Pengaruh Pesan Kampanye Public Relations “Uncover Your Stories” Terhadap Brand Awareness Rollover Reaction: Survei pada Mahasiswa Program Studi Ilmu Komunikasi Angkatan 2021 Universitas Pakuan Bogor - Khairunnisa, Dita Najla; Yuningsih, Siska (PT Literasi Nusantara Publisher, 2026)
The public relations campaign “Uncover Your Stories” launched by the local beauty brand Rollover Reaction aims to encourage and support women to love and appreciate themselves, as well as to reject lowering their self-worth for the sake of a partner, which may potentially lead to violence in relationships. This study aims to measure the extent of the influence of public relations campaign messages on Rollover Reaction’s brand awareness. This research employs a quantitative approach using a survey method involving 70 respondents, who are Communication Science students from the Class of 2021 at Universitas Pakuan Bogor, selected through an accidental sampling technique from a total population of 234 individuals. The variables examined include public relations campaign messages as the independent variable and brand awareness as the dependent variable. The results show that the public relations campaign messages are rated very positively, while brand awareness is categorized as good. Furthermore, there is a strong influence between campaign messages and brand awareness, with a correlation value of 0.850 and a contribution of 72%, while the remaining 28% is influenced by other factors.